The Interplay between Myc and CTP Synthase in Drosophila. - Gabriel N Aughey; Stuart J Grice; Ji-Long Liu (PLoS Genetics)
CTP synthase (CTPsyn) is essential for the biosynthesis of pyrimidine nucleotides. It has been shown that CTPsyn is incorporated into a novel cytoplasmic structure which has been termed the cytoophidium. Here, we report that Myc regulates cytoophidium formation during Drosophila oogenesis. We have found that Myc protein levels correlate with cytoophidium abundance in follicle epithelia. Reducing Myc levels results in cytoophidium loss and small nuclear size in follicle cells, while overexpression of Myc increases the length of cytoophidia and the nuclear size of follicle cells. Ectopic expression of Myc induces cytoophidium formation in late stage follicle cells. Furthermore, knock-down of CTPsyn is sufficient to suppress the overgrowth phenotype induced by Myc overexpression, suggesting CTPsyn acts downstream of Myc and is required for Myc-mediated cell size control. Taken together, our data suggest a functional link between Myc, a renowned oncogene, and the essential nucleotide biosynthetic enzyme CTPsyn.